Репрезентація синонімів у багатомовному електронному словнику з гідротурбінної термінології - Купріянов, Євген Валерійович (Гродненский государственный университет им. Я. Купалы, 2009)
The present article is devoted to the representation of synonyms in electronic dictionary on hydroturbines. The origins of synonyms in English and Spanish hydroturbine terminology are considered. A necessity of background knowledge and notions about conceptual field, in which synonymic terms are described, is grounded. To solve a problem of translation of special terms, especially in cases of their different interpretations, from Ukrainian into foreign languages and vice versa are proposed. New ways of representing synonymic terms in electronic dictionary are considered
Keywords: лексикографічна репрезентації синонімів; термінологічна лексика; синонімічні відношення; терміни-синоніми; термінологічні дублети